(untitled) (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To compare the postoperative outcome in patients who underwent arthroscopic single-bundle non-anatomic reconstruction of anterior cruciate ligament (ACL) through transtibial portal technique for femoral tunnel placement versus single-bundle anatomic ACL reconstruction through anteromedial portal technique for femoral tunnel placement. Methods: This retrospective comparative study was conducted on 120 patients who underwent ACL reconstruction in Combined Military Hospital Lahore and Rawalpindi between March 2012 and March 2015 were included. Group 1 had ACL reconstruction through Transtibial (TT) Portal and in Group 2 Anteromedial (AMP) portal was used for femoral tunnel placement. At a minimum follow-up of 1 year (13-25 months), the clinical and functional outcomes were obtained and analyzed. Results: Mean Tegner-Lysholm score improved from 41 preoperatively to 80 (fair) in TT portal group and from 42.2 to 85 (good) in AMP Portal Group. Mean Knee Injury and Osteoarthritis Outcome Score (KOOS) improved from 48.8 and 47.5 to 81 and 83 in TT portal group and AMP portal group respectively. The difference in post-op scores did not show significant difference between two groups (p>0.05). Residual anterior laxity was found in 11 (18.3%) patients in TT portal group compared to 10 (16.7%) patients in AM portal group (p>0.05). Out of these patients pivot shift test was abnormal in 8 (13.3%) patients in TT portal group and 3 (5%) patients in AMP portal group and this difference was significant (p<0.05). Conclusion: AMP portal technique for femoral tunnel placement leading to anatomic single-bundle ACL reconstruction is better than non-anatomic TT portal technique in overall postoperative clinical outcomes. Though anterior tibial translation is not much different but rotary stability improves significantly with femoral tunnel placement through anteromedial (AMP) portal. Key Words: ACL reconstruction, Femoral tunnel, Transtibial portal, Anteromedial portal